Stabilization of dentin matrix after cross-linking treatments, in vitro - Scheffel, Debora L. S. [UNESP]; Hebling, Josimeri [UNESP]; Scheffel, Regis H.; Agee, Kelli A.; Cadenaro, Milena; Turco, Gianluca; Breschi, Lorenzo; Mazzoni, Annalisa; Souza Costa, Carlos A. de [UNESP]; Pashley, David H. (Elsevier B.V., 2014)
Objectives: To evaluate the effect of EDC on elastic modulus (E), MMPs activity, hydroxyproline (HYP) release and thermal denaturation temperature of demineralized dentin collagen.Methods. Dentin beams were obtained from human molars and completely demineralized in 10 wt% H3PO4 for 18h. The initial E and MMP activity were determined with three-point bending and microcolorimetric assay, respectively. Extra demineralized beams were dehydrated and the initial dry mass (DM) was determined. All the beams were distributed into groups (n = 10) and treated for 30s or 60s with: water, 0.5 M, 1 M or 2 M EDC or 10% glutaraldehyde (GA). After treatment, the new E and MMP activity were redetermined. The beams submitted to DM measurements were storage for 1 week in artificial saliva, after that the mass loss and HYP release were evaluated. The collagen thermal denaturation temperature (TDT) was determined by DSC analysis. Data for E, MMP activity and HYP release were submitted to Wilcoxon and Kruskal-Wallis or Mann-Whitney tests. Mass loss and TDT data were submitted to ANOVA and Tukey tests at the 5% of significance.Results. EDC was able to significantly increase collagen stiffness in 60s. 10% GA groups obtained the highest E values after both 30 and 60s. All cross-linking agents decreased MMP activity and HYP release and increased TDT temperature. Significant differences were identified among EDC groups after 30 or 60s of cross-linking, 1 M or 2 M EDC showed the lowest MMP activity.Significance. Cross-linking agents are capable of preventing dentin collagen degradation. EDC treatment may be clinically useful to increase resin-dentin stability. (C) 2013 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
Keywords: MMPs; Collagen; Dentin; Cross-linkers; Glutaraldehyde; EDC